Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208654
|View full text |Cite
|
Sign up to set email alerts
|

Enabling self, intimacy and a sense of home in dementia

Abstract: Design and digital technologies to support a sense of self and human relationships for people living with dementia are both urgently needed. We present an enquiry into design for dementia facilitated by a public art commission for an adult mental health unit in a hospital in the UK. The interactive art piece was informed by the notion of personhood in dementia that foregrounds the person's social being and interpersonal relationships as sites where self is maintained and constructed. How clients, clients' fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 22 publications
3
92
0
Order By: Relevance
“…For example, in recent research that explored the possibilities of technology for improving life for patients suffering from dementia, the self is described as something malleable, historical, and social, for which interpersonal relationships are described as "sites where self is maintained and constructed" (Wallace, Thieme, Wood, Schofield, & Olivier, 2012, p. 2629) "through reflection, storytelling and dialogue" (Wallace et al, 2013(Wallace et al, , p. 2617). This suggests that the self is radically relational on an ontological level (see also Eriksson, Artman, & Swartling, 2013;Sun, Ding, Lindtner, Lu, & Gu, 2014).…”
Section: Hci Literature Problematizing the Selfmentioning
confidence: 99%
“…For example, in recent research that explored the possibilities of technology for improving life for patients suffering from dementia, the self is described as something malleable, historical, and social, for which interpersonal relationships are described as "sites where self is maintained and constructed" (Wallace, Thieme, Wood, Schofield, & Olivier, 2012, p. 2629) "through reflection, storytelling and dialogue" (Wallace et al, 2013(Wallace et al, , p. 2617). This suggests that the self is radically relational on an ontological level (see also Eriksson, Artman, & Swartling, 2013;Sun, Ding, Lindtner, Lu, & Gu, 2014).…”
Section: Hci Literature Problematizing the Selfmentioning
confidence: 99%
“…More recent work targeted specifically to people with dementia was done by Wallace and colleagues (Wallace et al, 2012) (Wallace et al, 2013). In the "Tales of I" project (Wallace et al, 2012) they designed a system comprised of a wall cabinet holding several snow globes that encased objects relating to topics like soccer, holidays or local and a television cabinet with a mold to hold a globe.…”
Section: Tangible Computing For Seniors' Reminiscencementioning
confidence: 99%
“…In the "Tales of I" project (Wallace et al, 2012) they designed a system comprised of a wall cabinet holding several snow globes that encased objects relating to topics like soccer, holidays or local and a television cabinet with a mold to hold a globe. Through RFID tags in the globe the TV could read the correct topic and start the corresponding film.…”
Section: Tangible Computing For Seniors' Reminiscencementioning
confidence: 99%
“…Several works [9,10] investigated the television as a medium to provide media from the past or personalized media to people with dementia and [11] found in an observation that generic video triggered more diverse comments and a broader spectrum of conversation topics in people with dementia. Thus, research showed that contents targeted to the individuals were catalysts for reminiscence and communication with others.…”
Section: Current Multimedia Applications For Dementia Patientsmentioning
confidence: 99%